The Role Of E-Learning Increasing The Efficiency And Effectiveness Of University Education - سهى سنكري (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research dealt with clarifying the nature of university education and the need for e-learning, while identifying the most important areas for benefiting from e-learning methods in the field of university education, as well as the most important requirements for increasing the efficiency and effectiveness of university education by making use of e-learning methods, and by reviewing some Arab and foreign experiences and by returning to studies Many results have been reached, the most important of which is that it is possible to benefit from information technologies (of various types) and to apply e-learning methods in university education, and it is also possible to increase the efficiency and effectiveness of education through the availability of a set of technical and cognitive requirements necessary to take advantage of the methods E-Learning. Which leads to rapid development in the fields of information technology and its multiple uses in university education, which requires the need to think about how to adapt the means and methods of e-learning in a way that can fit with the nature of university education, especially after the increased need for academic graduates in the information technology environment. The research concluded with a number of recommendations One of the most important is the enactment of legislation and policies that regulate e- learning to give legitimacy to the work environment.